The Church of England and the Second World War : Ethical Traditions in Anglican Public Theology - Alexander, John D., (Anglican-Episcopal Theology and History ;, 2025)
In The Church of England and the Second World War , John D. Alexander analyses how historic Christian ethical traditions influenced the Church of England's contributions to British pre-war and wartime public policy debates. These traditions include just war, holy war, pacifism, and Christian realism as deployed by such diverse Anglican figures as Cosmo Gordon Lang, William Temple, Herbert Hensley Henson, George Bell, Cyril Forster Garbett, Charles Raven, Percy Hartill, Evelyn Underhill, Vera Brittain, and James Parkes. Additional themes include war as divine judgement, humanitarian intervention, and Church of England responses to the Holocaust. As a case study in the application of Christian ethical traditions, this book makes vital connections between Anglican studies, international relations theory, and the diplomatic, military, and humanitarian challenges of the mid-twentieth century.